A Study on Scope and Developments of Organic Synthesis in Boric Acid: Recent developments and applications of boric acid in organic synthesis (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Boric acid [H3BO3] was a central element in organic synthesis in recent years. This review provides a summary of recent developments in the fields of catalyzed boric acid transformation in particular sterilization, trans esterification, addition of aza-Michael and thia-Michael, condensation, friedal reactions, halogenation, ipso substitution, decarboxylation, protection and deprotection, amidation and transamination reactions, multicomponent reactions, and more. In forming various biologically significant organic compounds recorded during the last decade, boric acid has emerged as an effective, mild, commercially available, inexpensive catalyst.